(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study explores the impact of Enterprise Resource Planning (ERP) systems on Human Resource Management (HRM) within the private sector of Pune, focusing on the concept of ERP systems, current challenges, and stakeholder satisfaction. ERP systems are designed to integrate and streamline business processes, including HR functions such as payroll and recruitment. This research utilizes both primary and secondary data collected through surveys and literature review to assess how ERP systems are perceived, the problems encountered, and the level of stakeholder satisfaction. The study reveals significant variability in the perception of ERP systems across different IT sectors, with notable challenges including integration issues, user training, data accuracy, and system downtime. Stakeholder satisfaction is mixed, with some expressing high contentment and others showing dissatisfaction. Recommendations include enhancing customization and integration capabilities, improving user training and support, strengthening data management, addressing cost and vendor support issues, and promoting effective communication. These measures aim to better align ERP systems with sector-specific needs, improve overall satisfaction, and enhance the effectiveness of ERP implementations.